7th. Int. Conf. On Thermal, Mechanical and Multiphysics Simulation and Experiments in Micro-Electronics and Micro-Systems
DOI: 10.1109/esime.2006.1643991
|View full text |Cite
|
Sign up to set email alerts
|

Using ElectroMechanical Buckling for Measuring Residual Stress

Abstract: In this work, a new test structure and method for measuring residual stress is presented. The test structure is a single clamped-clamped beam with electrodes symmetrically positioned along both sides of the beam. The electromechanical buckling response is used to measure the residual stress. It is shown that a single test structure of the proposed design may be used to measure both compressive and tensile residual stresses in a continuous wide range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This means that for small deflections the stiffness of the system vanishes, and this is a bifurcation transition of the equilibrium state [10]. This bifurcation transition is related to the phenomenon of electromechanical buckling [11].…”
Section: Side Pull-in Of Individual Comb Fingersmentioning
confidence: 99%
“…This means that for small deflections the stiffness of the system vanishes, and this is a bifurcation transition of the equilibrium state [10]. This bifurcation transition is related to the phenomenon of electromechanical buckling [11].…”
Section: Side Pull-in Of Individual Comb Fingersmentioning
confidence: 99%
“…The electromechanical system is governed by the following nonlinear integral-differential equation [7], [9]:…”
Section: Equation Of Motionmentioning
confidence: 99%
“…An analytical approach and a reduced-order model to investigate the behavior of electrically actuated microbeam-based MEMS are presented in [5] by Younis et al Nayfeh et al [6] studied the pull-in instability in MEMS resonators and established that characteristics of the pull-in phenomenon in the presence of alternate current (AC) loads differ from those under purely direct current (DC) loads. A new test structure and method for measuring residual stresses was presented by Abu-Salih and Elata [7]. They showed that a single test structure of the proposed design may be used to measure compressive and tensile residual stress in a continuous wide range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation